The Impact of Mandatory Auditor Tenure Disclosures on Ratification Voting, Auditor Dismissal, and Audit Pricing* - Dunn, Ryan T.; Lundstrom, Nathan G.; Wilkins, Michael S. (Contemporary Accounting Research, 2021)
ABSTRACT Recent amendments to Auditing Standard (AS) 3101 require disclosure of the initial year of the auditor‐client relationship in the audit report. As the standard was being discussed, auditors, clients, and some PCAOB members expressed reservations about the necessity of tenure disclosures and were particularly concerned about disclosing tenure in the audit report. Our purpose is to investigate whether the tenure disclosures mandated by AS 3101 are associated with changes in stakeholder behavior. We predict and find that after the implementation date, ratification votes against the auditor and the probability of subsequent auditor dismissal increase for long‐tenured versus short‐tenured auditors. Results from a path analysis further suggest that the relative increase in dismissal for long‐tenured auditors appears to be influenced directly through tenure disclosures and indirectly through ratification voting. We also predict and find that negotiating power decreases for long‐tenured auditors as evidenced by lower audit fees. Our results are comparable for companies that voluntarily disclosed and companies that did not disclose auditor tenure in their proxy statements prior to the AS 3101 amendment. Overall, our study suggests that mandatory disclosure of auditor tenure in the audit report significantly affects stakeholder behavior. The PCAOB should consider our findings carefully as they evaluate whether AS 3101 is achieving its intended purpose.